Stakeholders' Perceived Barriers and Successes of Quality Improvement Programs for Patients With Diabetes; Comment on "Quality and Performance Measurement in Primary Diabetes Care: A Qualitative Study in Urban China" - Ana Neumann (Kerman University of Medical Sciences, 2023)
Rasooly et al performed a qualitative evaluation to characterize the experiences of 26 stakeholders with the implementation of diabetes-related quality and performance measures delivered in primary healthcare to patients with diabetes in metropolitan China. Results from this cross-sectional investigation identified relevant gaps in primary care delivery for people with diabetes from one major center in China. As diabetes is a prevalent condition worldwide, lessons learned from this research can be useful to guide, refine, and improve quality measurement evaluations in primary care in China and other countries. In this commentary, we comment on the strengths and weaknesses of the study, suggest future directions, and discuss how lessons learned from this research can be helpful to guide, refine, and improve the quality measurement of diabetes care in other countries.